KARAKTERISTIK EKOLOGI MANGROVE DI KAWASAN SILVOAKUAKULTUR - Muarif Muarif; Samun M (JURNAL MINA SAINS, 2021)
The development of mangrove by silvoaquaculture approach is an integrating between mangrove conservation and economic improvement of coastal communities by aquaculture production. The study aims to determine the ecological characteristics of mangroves in silvoaquaculture areas. The research locations include Karangsong, Brondong, and Pabean Ilir in Indramayu Regency and use a survey technique using the quadrant transect method. The silvoaquaculture pond area in Indramayu Regency has five types of mangroves, namely Avicennia marina, Avicennia alba, Rhizophora apiculata, Rhizophora mucronata, and Rhizophora stylosa. Rhizophora mucronata is the dominant mangrove species. The best mangrove ecological conditions are found in empang parit and komplangan ponds, so based on the ecological characteristics of mangroves, it is recommended that the development of silvoaquaculture ponds use empang parit or komplangan type of pond.